2010
DOI: 10.4238/vol9-3gmr841
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis and karyotypes of three species of water striders (Gerridae, Heteroptera)

Abstract: ABSTRACT. Although they are of economic importance, there have been few cytogenetic studies of the Gerridae (Heteroptera) in Brazil. We examined spermatogenesis (meiosis and spermiogenesis) and nucleolar behavior in three species of the family Gerridae. Brachymetra albinerva and Halobatopsis platensis were found to have a chromosome complement of 2n = 25 (24A + X0) and Cylindrostethus palmaris 2n = 29 (28A + X0) chromosomes. Fifteen individuals of these species were collected from the reservoir of São José do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…A peculiarity observed during spermiogenesis of M. brasiliensis was the presence of a vesicle in the spermatids, which has not been observed in the terrestrial (Souza et al, 2007a(Souza et al, ,b, 2008(Souza et al, , 2009) and aquatic species (Castanhole et al, , 2010 studied. Thus, we emphasize that ultrastructural studies are required to describe this structure in more detail in order to clarify its relationship with the formation of sperm.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A peculiarity observed during spermiogenesis of M. brasiliensis was the presence of a vesicle in the spermatids, which has not been observed in the terrestrial (Souza et al, 2007a(Souza et al, ,b, 2008(Souza et al, , 2009) and aquatic species (Castanhole et al, , 2010 studied. Thus, we emphasize that ultrastructural studies are required to describe this structure in more detail in order to clarify its relationship with the formation of sperm.…”
Section: Discussionmentioning
confidence: 86%
“…The round spermatids presented two close corpuscles and during stretching, one corpuscle remained in the head and the other migrated to the initial part of the tail. At the end of the spermiogenesis process, these markings were not visualized (Castanhole et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It is believed that this characteristic is related to the great energy expenditure that these species need for survival in aquatic environments. Besides, it was observed that the testicular meiotic cells of terrestrial species are much smaller than those of aquatic ones, and when comparing the aquatic species studied nowadays, such cells of the families Gerridae (Castanhole et al, , 2010 and Veliidae are smaller than those of the family Notonectidae. According to Gäde et al (2004), N. glauca (Notonectidae) is very active and constantly swims around in captivity.…”
Section: Discussionmentioning
confidence: 99%